Section 40.1 of the American Law Institute's Corporate Governance Project: Restatement or Misstatement? - William J. Carney (Washington University Law Quarterly, 1988)
The American Law Institute's (ALI's) corporate governance project has generated the most heated debate in the history of that distinguished institution. Critics claim that the document is a radical proposal for reforming corporate law in a way that increases legal intrusions into the management of business, while supporters claim that the document is fairly reflective of much of the existing law, and that it clarifies and simplifies that law. This article focuses on what thus far has been the most heated part of the debate-the ALI's treatment of the duties and liabilities of corporate directors, set out in section 4.01 of the Principles of Corporate Governance. My thesis is that events of the 1960's and '70's led to attempts by both corporate officials and their attorneys to fend off what they saw as radical law reform, focused on federal chartering, with a series of aspirational documents intended to reassure critics that corporate managers and their attorneys were good and responsible citizens who were aware of their responsibilities. Accepting Berle & Mean's view of their own power, corporate managers claimed the mantle of good citizenship that Berle had ultimately bestowed upon them.
Keywords: Executives; American Law Institute